Gestão ambiental em parques nacionais e estaduais do Paraná: há comprometimento com as necessidades conservacionistas? - Oliveira, Alanda de (2024)
The institutionalization of the National System of Conservation Units (SNUC) in Brazilian environmental policy represented an important milestone in the management and implementation of Conservation Units. However, more than 20 years after its creation, the system of conservation units still faces several challenges in the management process, especially because these areas have their own particularities and limitations, which may vary according to their management category and management level. Given this perspective, Brazilian environmental agencies have several tools in the management process, and this paper discusses the characteristics of the Management Analysis and Monitoring System (SAMGe) developed by ICMBio and the Rapid Assessment and Prioritization of Conservation Unit Management method, known as RAPPAM, developed by the World Wide Fund for Nature (WWF). Thus, the present study aimed to investigate the environmental management process with the conservation of natural resources and biodiversity, through the application of the Rapid Assessment and Prioritization of Management Methodology (RAPPAM) with managers of State and National Parks in Paraná. The dissertation is structured around a theoretical discussion of the two management tools in the context of the Conservation Units in the state of Paraná. We then structure a discussion on the results obtained by applying RAPPAM, in which only one National Park and two State Parks provided feedback. It is important to highlight that the results obtained from the three responses collected reveal the main weaknesses that affect the Conservation Units. Among them, the lack of human and financial resources stands out, which, together, are directly related to the incidence of other conflicts within the Conservation Units. In addition, we point out a discussion on the lack of participation of managers in scientific research, caused mostly by work overload. Therefore, it is expected that this work can contribute to strengthening the management of the National and State Parks of Paraná and can encourage the process of forming new environmental public policies aimed at managing these areas.